SAND DISTRIBUTION MODELING OF MIDDLE MIOCENE RESERVOIR OF â€œEAST TARAKAN A FIELDâ€ IN EASTERN PART OF TARAKAN ISLAND, EAST KALIMANTAN - Priatin Hadi Widjaja; D. Noeradi (BULLETIN OF THE MARINE GEOLOGY, 2011)
The discovery well with initial name â€œEast Tarakan A-1â€ was drilled in February 2007 to a total vertical depth of 10,000 feet and encountered gas reservoir in Middle Miocene-age sands with deltaic sediment facies. The Field is structurally high, faulted to the Mengatal producing zones. This sandstone is hydrocarbon producer in most of onshore fields of Tarakan Island. â€œEast Tarakan Aâ€ Field has been suppported with 19 (nineteen) 2D Seismic data. There are three wells i.e: East Tarakan A-1, A2b and A3 with several logs data, mud log and biostratigraphic data. The study aims are firstly to built 3D structural model from time and depth structural maps based on seismic interpretation and well log analysis, secondly to create 3D properties model especially volume shale (V-shale) to get sand distribution. The sand distribution model is supported by 3D structural model, petrophysical analysis and seismic attributes as well as geo-statistic method. Based on petrophysical analysis and wells correlation, sand reservoir interval of Middle Miocene (Meliat Fm) can be devided into two zones respectively top to bottom; zone-1 dan zone-2. RMS Amplitude analysis has been used to help constrain the sand distribution. Sand distribution with two zones indicates that sand distribution of zone-1 and zone-2 are generally located in distributary channel delta. NTG Distribution model of zone-1 and zone-2 indicates that reservoir zone distributed in distributary sand with trend of west to east. NTG of zone-1 is relatively better reservoir than the zone-2. Keywords: Tarakan, Middle Miocene, V-shale, sand distribution, 3D model, NTG Sumur penemuan dengan nama inisial â€œEast Tarakan Aâ€ telah dibor pada Februari 2007 dengan total kedalaman 10.000 kaki dan dijumpai reservoir gas pada lapisan pasir berumur Miosen Tengah dengan fasies sedimen delta. Lapangan gas ini berupa struktur tinggian dan patahan bersebelahan dengan zona produksi Lapangan Mengatal. Batupasir sebagai batuan reservoir merupakan lapisan utama penghasil hidrokarbon di lapangan onshore di Pulau Tarakan. Lapangan â€œEast Tarakan Aâ€ didukung oleh data 19 penampang seismik 2D. Terdapat pula tiga sumur pemboran yaitu Tarakan A-1, A-2b dan A3 dengan beberapa data log sumur, mud log dan biostratigrafi. Studi ini dilakukan dengan maksud dan tujuan, pertama, membuat model stuktur geologi 3-dimensi dari peta struktur waktu dan kedalaman berdasarkan interpretasi seismic, analisis log sumur. Kedua, menghasilkan property model khususnya volume serpih (V-sh) untuk akhirnya memperoleh distribusi pasir. Model sebaran pasir didukung dengan model struktur 3D, analisis petrofisika dan atribut seismik serta metode geo-statistik. Based on petrophysical analysis and wells correlation, sand reservoir interval of Middle Miocene (Meliat Fm) can be devided into two zones respectively top to bottom; zone-1 dan zone-2. RMS Amplitude analysis has been used to help constrain the sand distribution. Sand distribution with two zones indicates that sand distribution of zone-1 and zone-2 are generally located in distributary channel delta. NTG Distribution model of zone-1 and zone-2 indicates that reservoir zone distributed in distributary sand with trend of west to east. NTG of zone-1 is relatively better reservoir than the zone-2. Berdasarkan pada analisis petrofisika dan korelasi antar sumur pemboran, lapisan reservoir pasir Miosen Tengah (Formasi Meliat) dibagi menjadi dua zona yaitu Zona-1 di bagian atas dan zona-2 di bawahnya. Analisis amplituda RMS pada data seismik digunakan untuk membantu penyebaran sedimen pasir. Sebaran pasir dengan dua zona menunjukkan secara umum keterdapatan pasir di area distributary channel delta. Model distribusi NTG (net to gross) pada zona-1 dan zona-2 memperlihatkan area reservoir berada di bagian pasir pada distributary channel dengan arah barat ke timur. NTG pada zona-1 relatif lebih baik daripada zona-2. Kata kunci: Tarakan, Miosen Tengah, V-serpih, sebaran pasir, NTG